Book Review : The Middle East Economies in Times of Transition - Devarajan, Shantayanan (Taylor and Francis, 2016)
In 2011, when the organizers of the International Economics Association decided to hold their 2014 World Congress in Jordan, they did not anticipate that the Middle East would be the center of one of the most important economic, political and social transitions of our time. The Arab Spring caught much of the world by surprise. Its aftermath has led to political unrest, violent conflict and deteriorating economic performance in the Middle East and North Africa (MENA) region. The organizers therefore asked Ishac Diwan and Ahmed Galal, two leading economists and experts on the region, to put together an edited volume from the papers at the World Congress relevant to the transition in the Middle East. This volume collects some of those papers, as well as a few others, to explain the factors that led to the Arab Spring and to anticipate some of its consequences. It provides a multidisciplinary “snapshot” of research on the transitions in MENA.